The ncRNA-AURKA Interaction in Hepatocellular Carcinoma: Insights into Oncogenic Pathways, Therapeutic Opportunities, and Future Challenges - Clarissa Joy C. Garcia; Luca Grisetti; Claudio Tiribelli; Devis Pascut (Life)
Hepatocellular carcinoma (HCC) represents a major public health concern and ranks among the leading cancer-related mortalities globally. Due to the frequent late-stage diagnosis of HCC, therapeutic options remain limited. Emerging evidence highlights the critical role of non-coding RNAs (ncRNAs) in the regulation of Aurora kinase A (AURKA), one of the key hub genes involved in several key cancer pathways. Indeed, the dysregulated interaction between ncRNAs and AURKA contributes to tumor development, progression, and therapeutic resistance. This review delves into the interplay between ncRNAs and AURKA and their role in hepatocarcinogenesis. Recent findings underscore the involvement of the ncRNAs and AURKA axis in tumor development and progression. Furthermore, this review also discusses the clinical significance of targeting ncRNA-AURKA axes, offering new perspectives that could lead to innovative therapeutic strategies aimed at improving outcomes for HCC patients.